A unique recipe for glass beads at Iron Age Sardis. (August 2019) - Van Ham-Meert, Alicia; Dillis, Sarah; Blomme, Annelore; Cahill, Nicholas; Claeys, Philippe; Elsen, Jan; Eremin, Katherine; Gerdes, Axel; Steuwe, Christian; Roeffaers, Maarten; Shortland, Andrew; Degryse, Patrick
Abstract: In large parts of the Mediterranean recipes for the earliest man-made glass changed from melting mixtures of crushed quartz pebbles and halophytic plant ashes in the Late Bronze Age to the use of quartz sands and mineral soda during the Early Iron Age. Not much is known about this transition and the experimental materials which would inevitably have been connected to such technological change. In this paper we present a unique snapshot of developments in glass technology in Anatolia during the Middle Iron Age, when glass is still a relatively rare commodity. The present work focusses on black glass beads decorated with yellow trails from eighth to seventh century BCE Sardis, glass beads that are very rare for this period, and on this site. A full elemental analysis of the beads was made, and Sr, Pb and B isotope ratios were determined. This study reveals the use of a combination of a previously unknown source of silica and of mineral soda, giving rise to elevated (granite-like) Sr isotope signatures, as well as high alumina and B concentrations. The yellow trails of glass on the beads consist of lead-tin yellow type II, lead stannate, showing the earliest occurrence of this type of opacifier/colourant so far, predating any other findings by at least four centuries. The production of these glass beads may be local to Sardis and experimental in nature. It is therefore suggested that Sardis may have played its role in the technological development of the glass craft during the Iron Age.